La Poste : pricing banking services - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
The French postal service provider, La Poste, has expanded to become one of Europe's leading logistics, corporate services and financial providers. La Poste has been successful in France, Germany and the United Kingdom and, given this success, the company's leaders are looking to expand into other French-speaking nations. This case study asks readers to assess the various options open to La Poste, and to decide the right choice for the company's marketing and management teams.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). La Poste: Pricing Banking Services. In International marketing (pp. 332-333). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Poste (France); Banks and banking -- Service charges -- Case studies; Pricing -- Case studies; Export marketing -- Case studies